EMPHASIZING THE CULTURAL AWARENESS IN TRANSLATION TEACHING - Roswani Siregar (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
Language is a means of communication closely related to social and cultural values. Translation as an intelligent process is a human activity that bridging the cultures. However it is not always easy when translator encounter the culture-items. This paper provided short overviewabout the emphasizing of culture awareness in translation teaching. The participants are the students of Law and Economic Faculty of Universitas Al-Azhar, Medan, Indonesia. Throughout the classroom activities: theories, discussion, practicing and response to questionnaire, the students encouraging to aware the cultural influences in translation. To do so, they need more practice with culture specific items that related to their subjects. Students were motivated in learning translation when they involve in discussion and using internet as the comparable source.  By emphasizing the importance of cultural awareness, the students impulse to learn more about other culture as well as improving their target language competence to avoid mistranslation.